Endoscopy in patients on antiplatelet or anticoagulant therapy: British Society of Gastroenterology (BSG) and European Society of Gastrointestinal Endoscopy (ESGE) guideline update. Issue 9 (6th August 2021) - Veitch, Andrew M; Radaelli, Franco; Alikhan, Raza; Dumonceau, Jean Marc; Eaton, Diane; Jerrome, Jo; Lester, Will; Nylander, David; Thoufeeq, Mo; Vanbiervliet, Geoffroy; Wilkinson, James R; Van Hooft, Jeanin E
Abstract : This is a collaboration between the British Society of Gastroenterology (BSG) and the European Society of Gastrointestinal Endoscopy (ESGE), and is a scheduled update of their 2016 guideline on endoscopy in patients on antiplatelet or anticoagulant therapy. The guideline development committee included representatives from the British Society of Haematology, the British Cardiovascular Intervention Society, and two patient representatives from the charities Anticoagulation UK and Thrombosis UK, as well as gastroenterologists. The process conformed to AGREE II principles and the quality of evidence and strength of recommendations were derived using GRADE methodology. Prior to submission for publication, consultation was made with all member societies of ESGE, including BSG. Evidence-based revisions have been made to the risk categories for endoscopic procedures, and to the categories for risks of thrombosis. In particular a more detailed risk analysis for atrial fibrillation has been employed, and the recommendations for direct oral anticoagulants have been strengthened in light of trial data published since the previous version. A section has been added on the management of patients presenting with acute GI haemorrhage. Important patient considerations are highlighted. Recommendations are based on the risk balance between thrombosis and haemorrhage in given situations.